Pengaruh Pertumbuhan UMKM Dan Tingkat Pengangguran Terhadap Pertumbuhan Ekonomi Di Indonesia - Lindah Tri Amanat Sari; Ladi Wajuba Perdini Fisabilillah (Universitas Negeri Surabaya, 2021)
The benchmark for achieving development in a country can be seen from its economic growth. The high economic growth reflects the high management of production factors in the country. MSMEs (Micro, Small, and Medium Enterprises) are considered to be a determining sector in increasing economic growth because they can manage all the factors that determine economic growth. Besides that, MSMEs can reduce unemployment by absorbing workers up to 119 million in 2019. Seeing this, the researcher wants to know whether there is an influence among the growth of MSMEs and the unemployment rate on economic growth in Indonesia after the economic crisis and before the Covid-19 pandemic with quantitative research methods. and the type of data is secondary data from 2000-2019. Classical assumption test of multiple linear regression was used as data analysis techniques in this study. The results obtained indicate that the MSMEs (Micro, Small, and Medium Enterprises) variable shows a negative effect on economic growth, while the unemployment variable shows a positive influence on economic growth